1999
DOI: 10.1590/s0301-80591999000400009
|View full text |Cite
|
Sign up to set email alerts
|

Predatory and parasitic activity of Aphelinus asychis (Hymenoptera: Aphelinidae) following exposure to the entomopathogenic fungus Paecilomyces fumosoroseus (Deuteromycotina: Hyphomycetes) under different humidity regimes

Abstract: The effect of the hyphomycete Paecilomyces fumosoroseus (Wise) Brown & Smith on the predatory and parasitic activity of Aphelinus asychis Walker, a common parasitoid of the Russian wheat aphid, Diuraphis noxia (Mordvilko), was investigated under three different humidities. Three cohorts of 20 female A. asychis were treated with 5.2 x 10(4) spores/cm² (twice the LD95 for D. noxia). Each female was then individually maintained in a ventilated Petri dish in which were placed three barley leaves and 20 third-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Parasitóides também são suscetíveis aos fungos entomopatogênicos, como observado para adultos de Aphelinus asychis Walker, parasitóide do pulgão-russodo-trigo, suscetíveis ao fungo Paecilomyces fumosoroseus em condições de alta umidade relativa (Mesquita et al 1999). Observações semelhantes foram feitas por Tounou et al (2003) Dados originais apresentados, para análise estatística os dados foram transformados em x + 0,5.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Parasitóides também são suscetíveis aos fungos entomopatogênicos, como observado para adultos de Aphelinus asychis Walker, parasitóide do pulgão-russodo-trigo, suscetíveis ao fungo Paecilomyces fumosoroseus em condições de alta umidade relativa (Mesquita et al 1999). Observações semelhantes foram feitas por Tounou et al (2003) Dados originais apresentados, para análise estatística os dados foram transformados em x + 0,5.…”
Section: Resultsunclassified
“…Poucos estudos foram conduzidos para determinar o efeito de microrganismos entomopatogênicos sobre Trichogramma ou outros parasitóides (Mesquita et al 1999, De La Rosa et al 2000, Tounou et al 2003, Santos Jr et al 2006.…”
Section: Palavras-chave: Fungo Entomopatogênico Parasitóide Biossegunclassified
“…However, the isolates of I. fumosorosea may not have resulted in the death of the females that came in contact with sprayed eggs as the fungus may have infected the body of T. pretiosum after death. Death due to infection with entomopathogenic fungi is reported for adults of the parasitoid, Aphelinus asychis Walker (Hymenoptera: Aphelinidae), treated with I. fumosorosea isolate ARSEF 4501 (Mesquita et al, 1999). Dalvi et al (2007) also do not report a statistical difference in the longevity of T. atopovirilia females that come in contact with L. lecanii and those in the control.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the existence of a high humidity boundary layer surrounding the nymphs. Research on the fungus with other insects has revealed a need for high humidity to promote germination and infection (Poprawski et al 1985;Mohamed and Varma 1992;Mesquita et al 1999). Conidia of P. fumosoroseus are rapidly killed by solar radiation, particularly UV-B Smits et al 1996Smits et al , 1997.…”
Section: Effects Of Abiotic Factorsmentioning
confidence: 99%